Zwischen Hochzeitsflug und Brudermord: reproduktive Taktiken bei Ameisenmännchen - Cremer, Sylvia; Heinze, Jürgen (Blick in die Wissenschaft)
Male dimorphism is not genetically determined, but is induced by environmental conditions particularly decreasing temperature and density.

Live and let die: Why fighter males of the ant Cardiocondyla kill each other but tolerate their winged rivals - Anderson, Carl; Cremer, Sylvia; Heinze, Jürgen (Behavioral Ecology)
Unlike most social insects, many Cardiocondyla ant species have two male morphs: wingless (ergatoid) males, who remain in the natal nest, and winged males who disperse but, strangely, before leaving may also mate within the nest. Whereas ergatoid males are highly intolerant of each other and fight among themselves, they tend to tolerate their winged counterparts. This is despite the fact that these winged males, like ergatoid males, represent mating competition. Why should ergatoid males tolerate their winged rivals? We developed a mathematical model to address this question. Our model focuses on a number of factors likely toinfluence whether ergatoid males are tolerant of winged males: ergatoid male–winged male relatedness, number of virgin queens, number of winged males, and the number of ejaculates a winged male has (winged males are sperm limited, whereas ergatoid males have lifelong spermatogenesis). Surprisingly, we found that increasing the number of virgin queens favors a kill strategy, whereas an increase in the other factors favors a let-live strategy; these predictions appear true for C. obscurior and for a number of other Cardiocondyla species. Two further aspects, unequal insemination success and multiple mating in queens, were also incorporated into the model and predictions made about their effects on toleration of winged males. The model is applicable more generally in species that have dimorphic males, such as some other ants, bees, and fig wasps.

Stress grows wings: Environmental induction of winged dispersal males in Cardiocondyla ants - Cremer, Sylvia; Heinze, Jürgen (Current Biology)
Dispersal is advantageous, but, at the same time, it implies high costs and risks. Due to these counteracting selection pressures, many species evolved dispersal polymorphisms, which, in ants, are typically restricted to the female sex (queens). Male polymorphism is presently only known from a few genera, such as Cardiocondyla, in which winged dispersing males coexist with wingless fighter males that mate exclusively inside their maternal nests. We studied the developmental mechanisms underlying these alternative male morphs and found that, first, male dimorphism is not genetically determined, but is induced by environmental conditions (decreasing temperature and density). Second, male morph is not yet fixed at the egg stage, but it differentiates during larval development. This flexible developmental pattern of male morphs allows Cardiocondyla ant colonies to react quickly to changes in their environment. Under good conditions, they invest exclusively in philopatric wingless males. But, when environmental conditions turn bad, colonies start to produce winged dispersal males, even though these males require a many times higher investment by the colony than their much smaller wingless counterparts. Cardiocondyla ants share this potential of optimal resource allocation with other colonial animals and some seed dimorphic plants.

Area and perimeter derivatives of a union of disks - Cheng, Ho; Edelsbrunner, Herbert (Computer Science in Perspective: Essays Dedicated to Thomas Ottmann)
We give analytic inclusion-exclusion formulas for the area and perimeter derivatives of a union of finitely many disks in the plane.

The weighted-volume derivative of a space-filling diagram - Edelsbrunner, Herbert; Koehl, Patrice (PNAS)
Computing the volume occupied by individual atoms in macromolecular structures has been the subject of research for several decades. This interest has grown in the recent years, because weighted volumes are widely used in implicit solvent models. Applications of the latter in molecular mechanics simulations require that the derivatives of these weighted volumes be known. In this article, we give a formula for the volume derivative of a molecule modeled as a space-filling diagram made up of balls in motion. The formula is given in terms of the weights, radii, and distances between the centers as well as the sizes of the facets of the power diagram restricted to the space-filling diagram. Special attention is given to the detection and treatment of singularities as well as discontinuities of the derivative.

Hierarchical Morse-Smale complexes for piecewise linear 2-manifolds - Herbert Edelsbrunner; Harer, John; Zomorodian, Afra (Discrete & Computational Geometry)
We present algorithms for constructing a hierarchy of increasingly coarse Morse-Smale complexes that decompose a piecewise linear 2-manifold. While these complexes are defined only in the smooth category, we extend the construction to the piecewise linearcategory by ensuring structural integrity and simulating differentiability. We then simplify Morse-Smale complexes by canceling pairs of critical points in order of increasing persistence.

Area, perimeter and derivatives of a skin curve - Cheng, Ho-Lun; Herbert Edelsbrunner (Computational Geometry: Theory and Applications)
The body defined by a finite collection of disks is a subset of the plane bounded by a tangent continuous curve, which we call the skin. We give analytic formulas for the area, the perimeter, the area derivative, and the perimeter derivative of the body. Given the filtrations of the Delaunay triangulation and the Voronoi diagram of the disks, all formulas can be evaluated in time proportional to the number of disks.

A multi-resolution data structure for two-dimensional Morse-Smale functions - Bremer, Peer; Edelsbrunner, Herbert; Hamann, Bernd; Pascucci, Valerio (Proceedings of the 14th IEEE Conference on Visualization)
We combine topological and geometric methods to construct a multi-resolution data structure for functions over two-dimensional domains. Starting with the Morse-Smale complex, we construct a topological hierarchy by progressively canceling critical points in pairs. Concurrently, we create a geometric hierarchy by adapting the geometry to the changes in topology. The data structure supports mesh traversal operations similarly to traditional multi-resolution representations.

Relaxed scheduling in dynamic skin triangulation - Edelsbrunner, Herbert; Üngör, Alper (Proceedings of the Japanese Conference on Discrete and Computational Geometry)
We introduce relaxed scheduling as a paradigm for mesh maintenance and demonstrate its applicability to triangulating a skin surface in R-3.

Slb/Wnt11 controls hypoblast cell migration and morphogenesis at the onset of zebrafish gastrulation - Ulrich, Florian; Concha, Miguel; Heid, Paul; Voss, Ed; Witzel, Sabine; Roehl, Henry; Tada, Masazumi; Wilson, Stephen; Adams, Richard; Soll, David; Heisenberg, Carl-Philipp J (Development)
During vertebrate gastrulation, highly coordinated cellular rearrangements lead to the formation of the three germ layers, ectoderm, mesoderm and endoderm. In zebrafish, silberblick (slb)/wnt11 regulates normal gastrulation movements by activating a signalling pathway similar to the Frizzled-signalling pathway, which establishes epithelial planar cell polarity (PCP) in Drosophila. However, the cellular mechanisms by which slb/wnt11 functions during zebrafish gastrulation are still unclear. Using high-resolution two-photon confocal imaging followed by computer-assisted reconstruction and motion analysis, we have analysed the movement and morphology of individual cells in three dimensions during the course of gastrulation. We show that in slb-mutant embryos, hypoblast cells within the forming germ ring have slower, less directed migratory movements at the onset of gastrulation. These aberrant cell movements are accompanied by defects in the orientation of cellular processes along the individual movement directions of these cells. We conclude that slb/wnt11-mediated orientation of cellular processes plays a role in facilitating and stabilising movements of hypoblast cells in the germ ring, thereby pointing at a novel function of the slb/wnt11 signalling pathway for the regulation of migratory cell movements at early stages of gastrulation.

Adhesive crosstalk in gastrulation - Montero, Juan; Heisenberg, Carl-Philipp J (Developmental Cell)
Recent studies show that signaling through integrin receptors is required for normal cell movements during Xenopus gastrulation. Integrins function in this process by modulating the activity of cadherin adhesion molecules within tissues undergoing convergence and extension movements.

Phosphoinositide 3-kinase is required for process outgrowth and cell polarization of gastrulating mesendodermal cells - Montero, Juan; Kilian, Beate; Chan, Joanne; Bayliss, Peter; Heisenberg, Carl-Philipp J (Current Biology)
Background: During vertebrate gastrulation, cell polarization and migration are core components in the cellular rearrangements that lead to the formation of the three germ layers, ectoderm, mesoderm, and endoderm. Previous studies have implicated the Wnt/planar cell polarity (PCP) signaling pathway in controlling cell morphology and movement during gastrulation. However, cell polarization and directed cell migration are reduced but not completely abolished in the absence of Wnt/PCP signals; this observation indicates that other signaling pathways must be involved. Results: We show that Phosphoinositide 3-Kinases (PI3Ks) are required at the onset of zebrafish gastrulation in mesendodermal cells for process formation and cell polarization. Platelet Derived Growth Factor (PDGF) functions upstream of PI3K, while Protein Kinase B (PKB), a downstream effector of PI3K activity, localizes to the leading edge of migrating mesendodermal cells. In the absence of PI3K activity, PKB localization and cell polarization are strongly reduced in mesendodermal cells and are followed by slower but still highly coordinated and directed movements of these cells. Conclusions: We have identified a novel role of a signaling pathway comprised of PDGF, PI3K, and PKB in the control of morphogenetic cell movements during gastrulation. Furthermore, our findings provide insight into the relationship between cell polarization and directed cell migration at the onset of zebrafish gastrulation.

The role of Ppt/Wnt5 in regulating cell shape and movement during zebrafish gastrulation - Kilian, Beate; Mansukoski, Hannu; Barbosa, Filipa; Ulrich, Florian; Tada, Masazumi; Heisenberg, Carl-Philipp J (Mechanisms of Development)
Wnt genes play important roles in regulating patterning and morphogenesis during vertebrate gastrulation. In zebrafish, slb/wnt11 is required for convergence and extension movements, but not cell fate specification during gastrulation. To determine if other Wnt genes functionally interact with slb/wnt11, we analysed the role of ppt/wnt5 during zebrafish gastrulation. ppt/wnt5 is maternally provided and zygotically expressed at all stages during gastrulation. The analysis of ppt mutant embryos reveals that Ppt/Wnt5 regulates cell elongation and convergent extension movements in posterior regions of the gastrula, while its function in more anterior regions is largely redundant to that of Slb/Wnt11. Frizzled-2 functions downstream of ppt/wnt5, indicating that it might act as a receptor for Ppt/Wnt5 in this process. The characterisation of the role of Ppt/Wnt5 provides insight into the functional diversity of Wnt genes in regulating vertebrate gastrulation movements. (C) 2003 Elsevier Science Ireland Ltd. All rights reserved.

Accumulating postzygotic isolation genes in parapatry: a new twist on chromosomal speciation - Navarro, Arcadio; Barton, Nicholas H (Evolution; International Journal of Organic Evolution)
Chromosomal rearrangements can promote reproductive isolation by reducing recombination along a large section of the genome. We model the effects of the genetic barrier to gene flow caused by a chromosomal rearrangement on the rate of accumulation of postzygotic isolation genes in parapatry. We find that, if reproductive isolation is produced by the accumulation in parapatry of sets of alleles compatible within but incompatible across species, chromosomal rearrangements are far more likely to favor it than classical genetic barriers without chromosomal changes. New evidence of the role of chromosomal rearrangements in parapatric speciation suggests that postzygotic isolation is often due to the accumulation of such incompatibilities. The model makes testable qualitative predictions about the genetic signature of speciation.

Chromosomal speciation and molecular divergence -- Accelerated evolution in rearranged chromosomes - Navarro, Arcadio; Barton, Nicholas H (Science)
Humans and their closest evolutionary relatives, the chimpanzees, differ in ∼1.24% of their genomic DNA sequences. The fraction of these changes accumulated during the speciation processes that have separated the two lineages may be of special relevance in understanding the basis of their differences. We analyzed human and chimpanzee sequence data to search for the patterns of divergence and polymorphism predicted by a theoretical model of speciation. According to the model, positively selected changes should accumulate in chromosomes that present fixed structural differences, such as inversions, between the two species. Protein evolution was more than 2.2 times faster in chromosomes that had undergone structural rearrangements compared with colinear chromosomes. Also, nucleotide variability is slightly lower in rearranged chromosomes. These patterns of divergence and polymorphism may be, at least in part, the molecular footprint of speciation events in the human and chimpanzee lineages.

The erratic path towards complexity - Barton, Nicholas H; Zuidema, Willem (Current Biology)
Artificial Life models may shed new light on the long-standing challenge for evolutionary biology of explaining the origins of complex organs. Real progress on this issue, however, requires Artificial Life researchers to take seriously the tools and insights from population genetics.

The effects of genetic and geographic structure on neutral variation - Charlesworth, Brian; Charlesworth, Deborah; Barton, Nicholas H (Annual Review of Ecology and Systematics)
Variation within a species may be structured both geographically and by genetic background. We review the effects of such structuring on neutral variants, using a framework based on the coalescent process. Short-term effects of sex differences and age structure can be averaged out using fast timescale approximations, allowing a simple general treatment of effective population size and migration. We consider the effects of geographic structure on variation within and between local populations, first in general terms, and then for specific migration models. We discuss the close parallels between geographic structure and stable types of genetic structure caused by selection, including balancing selection and background selection. The effects of departures from stability, such as selective sweeps and population bottlenecks, are also described. Methods for distinguishing population history from the effects of ongoing gene flow are discussed. We relate the theoretical results to observed patterns of variation in natural populations.

On the maintenance of reproductive isolation in a mosaic hybrid zone between the toads Bombina bombina and B. variegata - Vines, Timothy; Kohler, S C; Thiel, M; Ghira, Ioan; Sands, T R; Maccallum, Catriona; Barton, Nicholas H; Nürnberger, Beate (Evolution)
Mosaic hybrid zones arise when ecologically differentiated taxa hybridize across a network of habitat patches. Frequent interbreeding across a small-scale patchwork can erode species differences that might have been preserved in a clinal hybrid zone. In particular, the rapid breakdown of neutral divergence sets an upper limit to the time for which differences at marker loci can persist. We present here a case study of a mosaic hybrid zone between the fire-bellied toads Bombina bombina and B. variegata (Anura: Discoglossidae) near Apahida in Romania. In our 20 × 20 km study area, we detected no evidence of a clinal transition but found a strong association between aquatic habitat and mean allele frequencies at four molecular markers. In particular, pure populations of B. bombina in ponds appear to cause massive introgression into the surrounding B. variegata gene pool found in temporary aquatic sites. Nevertheless, the genetic structure of these hybrid populations was remarkably similar to those of a previously studied transect near Pescenica (Croatia), which had both clinal and mosaic features: estimates of heterozygote deficit and linkage disequilibrium in each country are similar. In Apahida, the observed strong linkage disequilibria should stem from an imperfect habitat preference that guides most (but not all) adults into the habitats to which they are adapted. In the absence of a clinal structure, the inferred migration rate between habitats implies that associations between selected loci and neutral markers should break down rapidly. Although plausible selection strengths can maintain differentiation at those loci adapting the toads to either permanent or temporary breeding sites, the divergence at neutral markers must be transient. The hybrid zone may be approaching a state in which the gene pools are homogenized at all but the selected loci, not dissimilar from an early stage of sympatric divergence.

Stochastic mapping of morphological characters - Huelsenbeck, John; Nielsen, Rasmus; Bollback, Jonathan P (Systematic Biology)
Many questions in evolutionary biology are best addressed by comparing traits in different species. Often such studies involve mapping characters on phylogenetic trees. Mapping characters on trees allows the nature, number, and timing of the transformations to be identified. The parsimony method is the only method available for mapping morphological characters on phylogenies. Although the parsimony method often makes reasonable reconstructions of the history of a character, it has a number of limitations. These limitations include the inability to consider more than a single change along a branch on a tree and the uncoupling of evolutionary time from amount of character change. We extended a method described by Nielsen (2002, Syst. Biol. 51:729-739) to the mapping of morphological characters under continuous-time Markov models and demonstrate here the utility of the method for mapping characters on trees and for identifying character correlation.

True and false gharials: A nuclear gene phylogeny of crocodylia - Harshman, John; Huddleston, Christopher; Bollback, Jonathan P; Parsons, Thomas; Braun, Michael (Systematic Biology)
The phylogeny of Crocodylia offers an unusual twist on the usual molecules versus morphology story. The true gharial (Gavialis gangeticus) and the false gharial (Tomistoma schlegelii), as their common names imply, have appeared in all cladistic morphological analyses as distantly related species, convergent upon a similar morphology. In contrast, all previous molecular studies have shown them to be sister taxa. We present the first phylogenetic study of Crocodylia using a nuclear gene. We cloned and sequenced the c-myc proto-oncogene from Alligator mississippiensis to facilitate primer design and then sequenced an 1,100-base pair fragment that includes both coding and noncoding regions and informative indels for one species in each extant crocodylian genus and six avian outgroups. Phylogenetic analyses using parsimony, maximum likelihood, and Bayesian inference all strongly agreed on the same tree, which is identical to the tree found in previous molecular analyses: Gavialis and Tomistoma are sister taxa and together are the sister group of Crocodylidae. Kishino-Hasegawa tests rejected the morphological tree in favor of the molecular tree. We excluded long-branch attraction and variation in base composition among taxa as explanations for this topology. To explore the causes of discrepancy between molecular and morphological estimates of crocodylian phylogeny, we examined puzzling features of the morphological data using a priori partitions of the data based on anatomical regions and investigated the effects of different coding schemes for two obvious morphological similarities of the two gharials.